Functional Employee Empowerment Strategy in the Department of Food Security and Agriculture of Bintan Regency Through a Dynamic Capabilities Approach - Maryani, Desi; Samin, Rumzi; Poti, Jamhur (LPPM Universitas Jambi, 2026)
This study analyzes the empowerment strategy of functional employees at the Department of Food Security and Agriculture of Bintan Regency through a Dynamic Capabilities approach. The research used a qualitative descriptive method with data collected through interviews, observations, and documentation. The findings show that employee empowerment has been implemented through the dimensions of sensing, seizing, and reconfiguring. Functional employees are involved in monitoring activities, technical programs, and organizational adaptation processes. However, several challenges remain, including competency gaps, limited technical training, and inadequate integration of information systems. The study concludes that strengthening competency development, adaptive management, and merit-based human resource systems is essential to support organizational effectiveness after bureaucratic simplification. The Dynamic Capabilities approach is relevant for improving the adaptability and performance of public organizations in facing administrative reform and environmental changes